Ang pagpapahalagang moral at espiritwal sa relasyong pangkapwa mula sa pilosopikal na pananaw - Ortinero, Aniceta M.
This paper explains the historical origin and the nature of two major components of values education: the moral and spiritual. The author highlights the humanitarian theory of moral ethics and analyzes the seven fundamental and supreme criteria of the moral and binding relationship between the moral and spiritual.
Binasa ng may-akda sa "Values Education Seminar-Workshop" sa College of Education, UP Diliman, noong Nobyembre 29, 1991.
Keywords: Moral education; Ethics; Spiritual life